Redox‐Active Microporous Covalent Organic Frameworks for Additive‐Free Supercapacitors - Guntermann, Roman; Rotter, Julian M.; Singh, Apeksha; Medina, Dana D.; Bein, Thomas (Small science, 2025)
Covalent Organic Frameworks In article number 2400585, Thomas Bein and co‐workers investigate the electrochemical performance of Wurster‐type covalent organic frameworks as electrode materials in supercapacitor devices. The direct growth of these highly porous and crystalline materials on stainless‐steel meshes mitigates the dependence on conductive additives, thereby revealing the ability to achieve high capacitance values in symmetric cells with ionic liquid electrolyte.